2019
DOI: 10.1038/s41467-019-11642-7
|View full text |Cite|
|
Sign up to set email alerts
|

Interplay of protein corona and immune cells controls blood residency of liposomes

Abstract: In vivo liposomes, like other types of nanoparticles, acquire a totally new ‘biological identity’ due to the formation of a biomolecular coating known as the protein corona that depends on and modifies the liposomes’ synthetic identity. The liposome–protein corona is a dynamic interface that regulates the interaction of liposomes with the physiological environment. Here we show that the biological identity of liposomes is clearly linked to their sequestration from peripheral blood mononuclear cells (PBMCs) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
188
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 195 publications
(191 citation statements)
references
References 61 publications
3
188
0
Order By: Relevance
“…First, we clarify that, following exposure to HP, grapholipoplexes get covered by a PC whose composition is affected by protein concentration. Evolution profiles of size and zeta-potential of biocoronated grapholipoplexes reported in Figure 2 closely resemble those previously reported for cationic liposome-protein complexes [51]. Considering the significant differences between grapholipoplexes and cationic liposomes in terms of shape and composition, this observation confirms that not-specific electrostatic interaction is the main driving force that regulates formation and equilibrium structure of coronated materials in biological fluids [33,52].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…First, we clarify that, following exposure to HP, grapholipoplexes get covered by a PC whose composition is affected by protein concentration. Evolution profiles of size and zeta-potential of biocoronated grapholipoplexes reported in Figure 2 closely resemble those previously reported for cationic liposome-protein complexes [51]. Considering the significant differences between grapholipoplexes and cationic liposomes in terms of shape and composition, this observation confirms that not-specific electrostatic interaction is the main driving force that regulates formation and equilibrium structure of coronated materials in biological fluids [33,52].…”
Section: Discussionsupporting
confidence: 87%
“…On the other side, pre-coating grapholipoplexes with artificial coronas formed at low protein concentrations may lead to high transfection efficiency and low cytotoxicity. In this regard, IgG-depleted plasma could be a convenient protein source to coat grapholipoplexes, as it may reduce undesired interactions with the immune system [51,54] and activate receptor-mediated endocytosis [55]. As many of us have shown, artificial coronas may remain stable upon re-exposure to biological media in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, protein glycation in diabetic patients 88 may affect their affinity to NPs, which may similarly influence the structural properties of the corona in addition to its composition. The platform is also suitable for the creation of "artificial coronas" for immune cell evasion 15 in dynamic incubation conditions, and assessing their stability over time under physiologically-relevant conditions. Notably, the effect of the pre-coating on the properties of the corona formed in the second incubation can be studied without separation steps or issues with NP aggregation.…”
Section: The Preclinical Workflow Provides a Convenient Tool For Holimentioning
confidence: 99%
“…These attempts are complicated by possible nanomaterial-induced conformational changes in the bound proteins, 7 which may escape the traditional methods of preclinical toxicology and can only be observed in in vivo. 8 It was recently demonstrated that the corona controls NP interactions with immune cells and pre-coating with artificial coronas prepared in vitro 15 or in vivo 16 can be employed to extend their blood circulation times and control biodistribution. Identical NPs may also form coronas with different sizes and compositions in different individuals, due to the effect of individual variation and disease on plasma composition or protein structure.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, it is important to understand the interactions occurring at the interface between NPs and biological fluids to predict the fate of injected NPs. It is commonly accepted that the interaction of the NPs and biological fluids is a consequence of several factors.NP size, shape, charge, or coating agents are critical [62][63][64][65][66][67][68][69], but the characteristics of the biological fluids are also very important (ionic strength, protein concentration, pH, and temperature) [70]. Once NPs are exposed to biological fluids, they interact with active biomolecules (mostly proteins, but also sugars, nucleic acids, and lipids) and PC is formed around them by the unspecific absorption of proteins on the surface of the NPs.…”
Section: Formation Of Protein Corona: Effect On Np-based Immunotherapymentioning
confidence: 99%